The psychological factor `self-blame` predicts overuse injury among top-level Swedish track and field athletes: a 12-month cohort study - Timpka, T.; Jacobsson, J.; Dahlström, Ö.; Kowalski, J.; Bargoria, V.; Ekberg, J.; Nilsson, S.; Renström, P. (British Journal of Sports Medicine, 2015)
Background Athletes` psychological characteristics are important for understanding sports injury mechanisms. We examined the relevance of psychological factors in an integrated model of overuse injury risk in athletics/track and field.